ANALYSIS OF THE INFLUENCE BETWEEN FRAUD TRIANGLE AND PERFECTIONISM ON ACADEMIC FRAUD OF ACCOUNTING STUDENTS (CASE STUDE OF ACCOUNTING STUDENT IN SURABAYA) - Safalas, Malta Dirga; Andayani, Sari (Yayasan Education and Social Center, 2023)
Academic fraud in the world of lectures is a phenomenon that significantly tarnishes the name of education. Academic fraud students commit does not reflect their identity as educated individuals who have received instruction. This study aims to test, analyze, and prove the effect of pressure, opportunity, rationalization, and perfectionism on academic fraud committed by accounting students in Surabaya. This study used a proactive stratified random sampling technique and obtained a sample size of 93 students. The research method used is quantitative with multiple linear regression analysis using the SPSS Version 25 program. The results of this study indicate that pressure, opportunity, and perfectionism do not significantly affect the academic fraud of accounting students, as evidenced by the significance value> 0.05 in the hypothesis test results. At the same time, rationalization is proven to significantly affect academic fraud among accounting students, with a significance value in the hypothesis test of <0.05